Cambios en las relaciones de trabajo de la mujer en comunidades campesinas - Loayza Alatrista, Sulema (2006)
In the labor market deep transformations are taking place that demand a reformulation of the traditional concepts of work and employment. The impact of the market economy on rural economies is giving place to the restructuring of work relationships in the interior of the family units of production, with the woman’s growing and diversified participation in productive work. This article presents the changes that have occurred in the last fifteen years in the relationship of woman’s work in rural communities in the mountains of Peru.